RESEARCH METHODOLOGY OF APPROACH TO TREATMENT IN DIABETES (Archive of Conferences, 2022)
One of the most important issues in the field of psychology is the research methodology and organization of the study of the motivational-value characteristics of the approach to the treatment of diabetes. Therefore, in the study of the motivational-value characteristics of the individual's attitude to treatment, it is necessary to make a comprehensive and multifaceted analysis. Health is a priceless treasure not only for man but also for society. This is the first need of a person, which determines his ability to work and ensure his mature development. In Uzbekistan, great attention is paid to the health of citizens, one of the most basic human values.